Longitudinal association of shorter leukocyte telomere length with CSF biomarker dynamics across early Alzheimer's disease stages in at-risk individualsResearch in context - Blanca Rodríguez-Fernández; Armand González-Escalante; Patricia Genius; Tavia E. Evans; Paula Ortiz-Romero; Carolina Minguillón; Gwendlyn Kollmorgen; Nicholas J. Ashton; Henrik Zetterberg; Kaj Blennow; Juan Domingo Gispert; Arcadi Navarro; et al. (EBioMedicine)
Summary: Background: Short telomere length (TL), a hallmark of biological ageing, has been associated with an increased risk of Alzheimer's disease (AD), but its pathophysiological role remains unclear. This study explored the relationship between blood leukocyte TL (LTL), cerebrospinal fluid (CSF) AD biomarkers changes, and brain structure across early stages of the AD continuum. Methods: We included 346 cognitively unimpaired participants (aged 49–71) from the ALFA cohort, enriched for AD risk (53.2% APOE-ε4 carriers; 34% amyloid-positive). LTL was measured at baseline (visit 0) using quantitative PCR. Associations were assessed between baseline LTL and CSF biomarkers at visit 1 (mean follow-up from baseline = 3.98 years, SD = 1.02), and with changes in CSF biomarkers between visits 1 and 2 (mean interval = 3.45 years, SD = 0.58). Cortical thickness in ageing- and AD-vulnerable brain regions was evaluated by magnetic resonance imaging (MRI) at visit 1. Analyses were stratified by APOE-ε4 status and amyloid-tau (AT) profiles. Mediation models tested whether CSF biomarkers mediated LTL-cortical thickness associations. Findings: Shorter LTL was associated with higher astrocytic reactivity at visit 1 and with increased synaptic dysfunction over time. Among APOE-ε4 carriers and AT-positive individuals, shorter LTL was associated with higher p-tau181 and neurodegeneration markers. Shorter LTL was associated with greater cortical thickness in ageing- and AD-vulnerable regions, partially mediated by astrocytic reactivity biomarkers. Interpretation: These findings suggest that shorter telomeres are associated with early AD-related biological changes, potentially via mechanisms involving astrocytic reactivity and brain structural alterations. LTL may serve as an early marker of vulnerability to neurodegenerative processes in at-risk populations. Funding: AARG-19–618265; PI19/00119; LCF/PR/GN17/10300004; TriBEKa-17–519007; # SLT002/16/00201.